2004
DOI: 10.1055/s-2004-832647
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 13-epi-Sclareol on the Bacterial Respiratory Chain

Abstract: 13-epi-sclareol is a labdane-type diterpene isolated from the resinous exudates of the medicinal plant species Pseudognaphalium cheiranthifolium (Lam.) Hilliard et Burtt. and P. heterotrichium (Phil.) A. Anderb. This compound has antibacterial activity only against Gram-positive bacteria, showing a bactericidal and lytic action. The interaction of 13- epi-sclareol with the bacterial respiratory chain was analyzed. The compound inhibited oxygen consumption of intact Gram-positive cells, but not with Gram-negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 16 publications
(27 reference statements)
0
27
0
Order By: Relevance
“…Different results were obtained in Gram positive bacteria treated with 13-epi-Sclareol 21 Tapia et al (2004) reported that this compound inhibited oxygen consumption in intact Gram-positive. In addition, the authors described that the diterpenoid was able to inhibit NADH oxidase and cytochrome C reductases activities suggesting that the target site of 13-epi-Sclareol was located between coenzyme Q and cytochrome C of the bacterial respiratory chain 21 .…”
Section: Mode Of Action Of Sclareol and 13-epi-sclareol On B Cinereamentioning
confidence: 93%
See 1 more Smart Citation
“…Different results were obtained in Gram positive bacteria treated with 13-epi-Sclareol 21 Tapia et al (2004) reported that this compound inhibited oxygen consumption in intact Gram-positive. In addition, the authors described that the diterpenoid was able to inhibit NADH oxidase and cytochrome C reductases activities suggesting that the target site of 13-epi-Sclareol was located between coenzyme Q and cytochrome C of the bacterial respiratory chain 21 .…”
Section: Mode Of Action Of Sclareol and 13-epi-sclareol On B Cinereamentioning
confidence: 93%
“…In addition, the authors described that the diterpenoid was able to inhibit NADH oxidase and cytochrome C reductases activities suggesting that the target site of 13-epi-Sclareol was located between coenzyme Q and cytochrome C of the bacterial respiratory chain 21 .…”
Section: Mode Of Action Of Sclareol and 13-epi-sclareol On B Cinereamentioning
confidence: 99%
“…This effect may be indicates that many chemical compounds interfering directly with electron transfer or uncoupled oxidative phosphorylation from electron transport. So, the aerobic synthesis of ATP is inhibited and the oxygen uptake is not inhibited (17). Also, it may be indicates a slight effect on the plasma membrane and increasing cells respiration for exhausting the energy compound present inside the cell before its death (20).…”
Section: Respiratory Activitymentioning
confidence: 99%
“…The quantity of oxygen consumed by the living cells (respiratory activity) in the presence or absence of the sublethal dose of the thienopyrimidine compound was determined as described by Tapia et al (17). The living cells of the tested bacterial species and fungi grown up to exponential phase were harvested by centrifugation (6000 g), washed with saline solution and resuspended to a concentration of one mg/mL cells (wet weight) in 50 mM phosphate buffer (pH 7.0).The cell suspension was added to a two mL chamber.…”
Section: Respiratory Activitymentioning
confidence: 99%
“…Plant-derived terpenoids [1] such as the diterpene alcohol Sclareol [2] are effective against cancer [1,[3][4][5][6][7][8][9][10][11][12][13], inflammation [1,14,15], and infection [16][17][18]. Sclareol further influences brain function [19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%